PERAN MANAGEMENT ACCOUNTING SYSTEM DALAM KETIDAKPASTIAN PADA ORGANISASI - David Efendi; Hermono Widiarto (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2017)
This paper aims to show the role of Management Accounting System (MAS) in conditions of uncertainty in the organization. MAS assists management in achieving its goals through the decision making process. Uncertainty is caused by the complexity and diversity of tasks that managers carry out in carrying out their duties. Many studies evaluate and analyze the relationship between MAS and task uncertainty and environmental uncertainty on managerial performance or organizational performance. The research findings show that MAS shows a significant role in improving managerial performance and organizational performance in times of task uncertainty and environmental uncertainty.